Rheumatoid Arthritis and Mental Health: An In-Depth Review - Toczek, Wiktoria; Bogdan , Klaudia; Jankowski , Mikołaj; Olszówka, Magdalena; Janicka, Urszula; Ciepluch, Natalia; Słomiński, Szymon Stanisław (Quality in Sport, 2025)
Background/Objective: Rheumatoid arthritis (RA) co-occurs with depression and anxiety, driven by shared inflammatory pathways, that impair quality of life and treatment response. This review synthesizes evidence on biological mechanisms, biomarkers, and therapeutic strategies targeting RA-related depression. Methods: Narrative synthesis of epidemiological, biomarker, pharmacological and lifestyle studies linking RA inflammation to mental health. Results: Pro-inflammatory cytokines (IL-6, TNF-α) mediate the RA-depression nexus, while elevated IL-6, TNF-α, and CRP levels can be used for predicting depression risk. IL-6 inhibitors, TNF inhibitors and JAK inhibitors demonstrate significant improvement in mental state of the patients. SSRIs/SNRIs provide help in maintaining high-minded mood and pain relief, while Mediterranean diet adherence can halve depression odds. Emerging preclinical data support neuroimmune modulators like aucubin targeting CXCL10/BTN3A2.​ Conclusion: Integrated care combining cytokine-targeted therapies, antidepressants, psychological interventions, and anti-inflammatory lifestyle measures optimizes outcomes for RA patients with depression, emphasizing early screening and holistic management.